2020
DOI: 10.1080/10410236.2020.1862449
|View full text |Cite
|
Sign up to set email alerts
|

Do People Actually “Listen to the Experts”? A Cautionary Note on Assuming Expert Credibility and Persuasiveness on Public Health Policy Advocacy

Abstract: The present work empirically explores whether experts are trusted more or more persuasive than an "average Joe" when engaging in policy advocacy on public health topics. I conducted a 2 (topic: climate change vs. COVID-19) X 2 (source: expert vs. nonexpert) experimental study with an US adult sample (N = 486). Using Bayes factors to quantify evidence for null and alternative hypothesis, I find substantial evidence that at least under the conditions present in the study, experts are perceived to be higher in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…As smart phone apps are often recommended for tracking and motivating physical exercise, it would be worthwhile to examine how wording of the text in smart phone apps influences usage of the app amongst men and women [ 104 ]. In addition, this study focused on featuring an expert (doctor), but the influence of the professional status of the endorser should also be examined [ 105 ]. The gender role identity of the endorser should also be manipulated and examined, in addition to the gender role identity of respondents, as well as the perceived fit/similarity of the endorser to the respondent.…”
Section: Discussionmentioning
confidence: 99%
“…As smart phone apps are often recommended for tracking and motivating physical exercise, it would be worthwhile to examine how wording of the text in smart phone apps influences usage of the app amongst men and women [ 104 ]. In addition, this study focused on featuring an expert (doctor), but the influence of the professional status of the endorser should also be examined [ 105 ]. The gender role identity of the endorser should also be manipulated and examined, in addition to the gender role identity of respondents, as well as the perceived fit/similarity of the endorser to the respondent.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical perspectives suggest that source credibility is a two-dimensional construct, with expertise and trustworthiness being the core components (Choi and Stvilia, 2015). Whilst research has indicated that information from experts is typically more influential to the public (Wathen and Burkell, 2002), it may not always be the case, as non-expert sources have also been found to be considered more trustworthy (Geiger, 2022). The emergence of the iInternet has further complicated the assessment of trustworthiness based on source reputation, as the ability to share information is not exclusive to those with the necessary “worth” to distribute it (Taraborelli, 2008).…”
Section: Sorting Fact From Fiction: What Is Information Credibility?mentioning
confidence: 99%
“…Advocates would benefit from assessing how to build trust with target populations. For example, when advocating for policy, neutral experts are trusted more than politicians (especially politicians of the opposite party; Flores et al., 2022), but not more than “the average Joe” (Geiger, 2022b). Overall, climate experts are more trusted and persuasive in policy advocacy when they show that they are adjusting their own behavior to reduce carbon emissions (Attari et al., 2019; Sparkman & Attari, 2020) and when they attempt to connect with their audiences' values (Geiger, Sarge, & Comfort, 2022).…”
Section: Trustingmentioning
confidence: 99%